Development of Android Physics Learning Tools Based on Local Wisdom Traditional Game Bola Boy as a Learning Source - Mudjid, Rosita Madjis; Supahar; Putranta, Himawan; Hetmina, Dickson Simonidez (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Teachers must develop learning tools that can assist students in making it easier to follow the course of learning and improve students’ abilities. Teachers can integrate local wisdom into learning tools that will have an impact on increasing student competence. The purpose of this research is to produce learning tools based on local wisdom that is suitable for use. The learning tools developed to consist of the lesson plan, student worksheets, and Android media. Based on the results of the feasibility assessment by several validators consisting of two experts, two physics teachers, and three colleagues, the learning tools developed are in a good category and are suitable for use with an average score between 3.80 to 4.40. Furthermore, 30 students tested the product to determine the readability of the product, namely android media as a learning media. Based on the results of the product trial analysis, it is known that the android media product is in the very good category and is worthy of being used as a learning resource on a larger scale with an average score of 4.10. This learning tool can be used as an alternative to contextual physics learning guidelines.